Šume crne johe (tip 91E0* Natura 2000, tip E.2.1.9. NKS) u Nacionalnom parku Plitvička jezera : Black alder forests (type 91E0* Natura 2000 type E.2.1.9. NHC) in the Plitvice Lakes National Park - Vukelić, Joso, inženjer šumarstva (Array, 2019)
The paper presents the first results of monitoring Natura 2000 habitat type 91E0*in the Plitvice Lakes National Park (Croatia). This type is represented in black alder forests (Alnus glutinosa /L./ Gaertn.) on an area of 44 ha. There, following the Braun-Blanquet method (1964), 25 plots were set up and relevés made, with 175 species of higher plant species recorded. Their environmental and sociological features suggest wetland and periodically flooded habitats with high ground water levels throughout the year, hence hygrophytes are decisive for the community structure. In addition, there is a moderate share of mesophilic species that are not present in the wetland black alder forests along the Sava and Drava rivers in the lowland part of northern Croatia. A comparison of black alder forests of the Plitvice Lakes NP with other black alder syntaxa in Croatia (Figure 2, Table 3) demonstrates that, together with other alder stands in the Dinaric region of Croatia, they belong to the group of wetland forests of the alliance Alnion glutinosae. Their differentiating species with regard to other syntaxa of the alliances Alnion glutinosae and Alnion incanae in Croatia are Fraxinus excelsior, Daphne mezereum, Viburnum lantana, Cirsium oleraceum, Crepis paludosa, Equisetum arvense, Paris quadrifolia, Thalictrum aquilegifolium, Valeriana dioica, Veratrum album, Acer pseudoplatanus, Chaerophyllum hirsutum, Lonicera xylosteum, Filipendula ulmaria, Knautia drymeia, Cruciata glabra. In addition, the researched stands in the Plitvice Lakes NP demonstrate individuality with regard to other stands of the Croatian Dinarides through the differentiating species of Phalaris arundinacea, Dactylorhiza maculata, Cirsium arvense, Primula vulgaris, Listera ovata, Carex acutiformis, C. paniculata, Succisa pratensis, Gentiana asclepiadea. Black alder forests in the Plitvice Lakes NP were created by successive processes in non-forest areas after their fall out of use (Figure 1).